Dual Defect‐Passivation Using Phthalocyanine for Enhanced Efficiency and Stability of Perovskite Solar Cells. Issue 1 (8th December 2020) - Hu, Qikun; Rezaee, Ehsan; Xu, Wangping; Ramachandran, Rajendran; Chen, Qian; Xu, Hu; EL‐Assaad, Tarek; McGrath, Dominic V.; Xu, Zong‐Xiang
Abstract: Semiconducting molecules have been employed to passivate traps extant in the perovskite film for enhancement of perovskite solar cells (PSCs) efficiency and stability. A molecular design strategy to passivate the defects both on the surface and interior of the CH3 NH3 PbI3 perovskite layer, using two phthalocyanine (Pc) molecules ( NP ‐SC6 ‐ZnPc and NP ‐SC6 ‐TiOPc) is demonstrated. The presence of lone electron pairs on S, N, and O atoms of the Pc molecular structures provides the opportunity for Lewis acid–base interactions with under‐coordinated Pb 2+ sites, leading to efficient defect passivation of the perovskite layer. The tendency of both NP ‐SC6 ‐ZnPc and NP ‐SC6 ‐TiOPc to relax on the PbI2 terminated surface of the perovskite layer is also studied using density functional theory (DFT) calculations. The morphology of the perovskite layer is improved due to employing the Pc passivation strategy, resulting in high‐quality thin films with a dense and compact structure and lower surface roughness. Using NP ‐SC6 ‐ZnPc and NP ‐SC6 ‐TiOPc as passivating agents, it is observed considerably enhanced power conversion efficiencies (PCEs), from 17.67% for the PSCs based on the pristine perovskite film to 19.39% for NP ‐SC6 ‐TiOPc passivated devices. Moreover, PSCs fabricated based on the Pc passivation method present a remarkable stability under conditions of high moisture and temperature levels. Abstract : Utilizing NP ‐SC6 ‐TiOPc and NP ‐SC6 ‐ZnPc as passivating agents on perovskite thin film through an antisolvent, improved performance and stability are achieved for perovskite solar cells. The highest power conversion efficiencies (PCEs) of 19.39% and 18.04% are obtained for NP ‐SC6 ‐TiOPc and NP ‐SC6 ‐ZnPc passivated devices, which is higher than that of the control devices without post‐treating the MAPbI3 films (PCE of 17.67%).